Crop diversification: an important way-out for doubling farmers’ income - Khanam, Rubina; Bhaduri, Debarati; Nayak, A. K. (Indian Farming, 2018)
Persistent low level of farmers’ income can cause serious adverse effect on the future of agriculture in the country. To secure future of agriculture and to improve livelihood of half of India’s population, adequate attention needs to be given to improve the welfare of farmers and raise agricultural income. Introduction, adaption and acceptance of new varieties as well as new and upcoming production technologies can potentially strengthen farmers’ cropping systems by increasing yields, improving drought resilience, boosting resistance to pests and diseases and also by capturing new market opportunities. There is a need to identify crops and varieties that may suit to a range of environments and farmers’ preferences. Crop diversification provides better conditions for food security and enables farmers to grow surplus products for sale at market and thus help to obtain increased income to meet other needs related to household well-being. Crop diversification can enable farmers to gain access to national and international markets with new products, food and medicinal plants. Diversifying from the monoculture of traditional staples can have important nutritional benefits for farmers in developing countries and can support a country for becoming more selfreliant in terms of food production. Diversification can also manage price risk, on the assumption that not all products will suffer low market prices at the same time and increase the profitability of the farming community.